Building open bridges: collaborative remixing and reuse of open educational resources across organisations - Coughlan, Tim; Pitt, Rebecca; McAndrew, Patrick (ACM Press, 2013)
In this paper we analyse the remixing and reuse of online learning materials offered as Open Educational Resources (OER). We explore the practices that developed as a set of course materials were released as OER from the UK, remixed for a US context by a cross-organisational, cross- cultural team, and then reused in a broad range of educational settings. We analyse the approaches taken during these remixing and reuse activities as novel forms of creative collaboration. As a basis for comparison, we explore similarities and differences with other Open practices. We identify how openness provoked novel inter- organisational collaboration and forms of ownership; define forms of open practice that need support, and present issues that should be considered in devising and supporting open projects in education and beyond.